An innovative small molecule for promoting neuroreparative strategies. Issue 10 (31st January 2018) - Colabufo, Nicola Antonio; Contino, Marialessandra; Cantore, Mariangela; Berardi, Francesco; Perrone, Roberto; Tonazzi, Annamaria; Console, Lara; Panaro, Maria Antonietta; Savolainen, Heli; Luurtsema, Gert
Abstract : In this study, a new regenerative strategy to treat several neurodegenerative diseases is suggested by the use of a multitarget approach induced by our small molecule, MC111 . Abstract : In this study, a new regenerative strategy to treat several neurodegenerative diseases is suggested by the use of a multitarget approach induced by our small molecule, MC111 . Considering the importance of P-gp and BCRP expression on stem cell differentiation and the involvement of TLR4 on neurodegeneration processes, we investigated the effect ofMC111, belonging to our library of P-gp active compounds on: (i) TLR4 signaling; (ii) P-gp and BCRP activity and expression; (iii) neurite sprouting. The observed findings exerted byMC111, open a new scenario for a multitarget and regenerative approach in neurodegenerative diseases encouraging the in vivo evaluation ofMC111 as new tool in neuroreparative medicine.